Candidates for Fertility-Sparing Surgery in Case of Ovarian Cancer - Gracia, Myriam; Alonso-Espías, María; Zapardiel, Ignacio (Seminars in Reproductive Medicine, 2025)
Ovarian cancer, a leading cause of gynecological cancer mortality, often affects women of reproductive age. Fertility-sparing surgery (FSS) has emerged as a viable option for selected patients with early-stage ovarian cancer who wish to preserve fertility. Patient and tumor selection criteria focus on preserving ovarian function and reproductive potential without compromising oncological safety. Optimal candidates are young, premenopausal women with disease confined to one ovary and favorable prognostic factors such as early FIGO stage, specific histologic subtypes, and good overall health. FSS typically involves unilateral salpingo-oophorectomy while preserving the uterus and contralateral ovary, achieving survival outcomes comparable to radical surgery in early-stage low-grade tumors. However, its application in higher-risk cases requires cautious evaluation. Multidisciplinary management, involving gynecologic oncologists and reproductive specialists, is essential for successful implementation of FSS, ensuring both oncological safety and preservation of reproductive potential. Long-term follow-up is critical to monitor recurrence and assess reproductive outcomes. Pregnancy after FSS is feasible, with timing guided by cancer type, stage, and individual circumstances. This review summarizes the current knowledge on FSS in ovarian cancer, emphasizing its relevance and the need for further research to refine patient selection and ensure optimal outcomes.
Keywords: ovarian cancer; fertility preservation; surgical treatment; fertility-sparing surgery; survival